Ensino paralelo na periferia: uma vis??o da educa????o ?? luz de Ferr??z - Santos, Maria Aparecida Costa dos (2011)
The present study is to understand the object of research education in the periphery from the perspective of one them: the writer Ferr??z. Ferr??z is a pseudonym of Reginaldo Faria da Silva, a name that has become a trademark of the resident community of Cap??o Redondo located in the Southwest Zone of S??o Paulo, which is synonymous with poverty, violence and abandonment. Despite the harsh reality, the peripheral devices and produce, in its peculiar way, literary, musical and theatrical craft. This phenomenon has grown over the years, through the encouragement and determination Ferr??z and his brothers , howevwe the results for education industry do not show betters results in formal learning of the residents of periphery, according to the national examinations evaluation. Ferrez learned to read and write in school, but it was in "college life" and became a writer, just as his life was transformed by the literature, seeks to transform the lives of others through the Literature Marginal, the actions cultural and educational spaces. Even living in a poor community and a deficient public school, how could Ferrez become a renowned writer? How did this learning? Inside or outside of school? These were the core issues that led the study in the attempt to define how learning takes place without following the training provided in studies of linear learning. For this study established the differential between the categories of education (formal, informal and non-formal) with the concepts and notions that appear in the works of Ferrez and with the possibility of developing a new concept in education - teaching parallel, educational process developed in the periphery. In addition to published works Ferrez, we were used as a source of Internet blogs, video interviews and documentaries. As we used the theoretical perspectives of Paulo Freire, Gaiatri Spivak, Maria da Gloria Gohn, Licia do Prado Valladares, Haroldo Torres and others.